Amyloid fibril formation by human stefin B: influence of the initial pH-induced intermediate state. (August 2002) - Žerovnik, E.; Turk, V.; Waltho, J. P.
Abstract : The amyloid fibril field is briefly described, with some stress put on differences between various proteins and possible role for domain swapping. In the main body of the text, first, a short review is given of the folding properties of both human stefins, α/β-type globular proteins of 53% identity with a known three-dimensional fold. Second, in vitro study of amyloid fibril formation by human stefin B (type I cystatin) is described. Solvents of pH 4.8 and pH 3.3 with and without 2, 2, 2-trifluoroethanol (TFE) were probed, as it has been shown previously that stefin B forms acid intermediates, a native-like and molten globule intermediate, respectively. The kinetics of fibrillation were measured by thioflavin T fluorescence and CD. At pH 3.3, the protein is initially in the molten globule state. The fibrillation is faster than at pH 4.8; however, there is more aggregation observed. On adding TFE at each pH, the fibril formation is further accelerated.